ЕРИТРОЇДНІ ЕЛЕМЕНТИ ГЕМОЛІМФИ ANADARA ІNAEQUІVALVІS (MOLLUSCA: ARCIDAE) В УМОВАХ ЕКСПЕРИМЕНТАЛЬНОЇ АНОКСІЇ: ФУНКЦІОНАЛЬНІ І МОРФОМЕТРИЧНІ ХАРАКТЕРИСТИКИ - Новицька, В. М.; Солдатов, О. О. (Marine Ecological Journal, 2023)
Influence of anoxia (exposure – 3 days) on functional, morphologic and cytometrical characteristics of hemolymph erythroid elements of bivalve mollusc Anadara inaequivalvis (Bruguiere, 1789) was investigated in experimental conditions Anoxia caused the hydration of cytoplasm and swelling of erythroid elements. The pattern of changes in erythrocyte indices (MCV, MCH, MCHC) and geometric parameters of cells confirmed that phenomenon. It was accompanied by a lysis of predominantly old cellular forms with lower osmotic resistance. Destruction of old erythroid forms resulted in relative increase in content of cells of earlier generation in the hemolymp which led to an increase in mean cell volume of a nucleus, content of basophilic granular inclusions in cytoplasm and stability of erythroid elements of the mollusc to osmotic shock.